Takhrij Hadis tentang Tatacara Berpuasa - Muhammad Tohir Ritonga (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to learn about the Hadith and its contents about the fasting ceremony, to make a scheme of the Sunnah Hadith about fasting, and to explain the examination of Sunnah hadith about Fasting ceremonies. This type of research uses descriptive qualitative research methods with a library survey approach, i.e. research supported by literature related to research issues. The results of this study show that first, the hadiths that describe fasting rituals in particular in the at-tis’ah pole were found quite a lot. He who eats because he forgets to fast, then it is a